A new Simple Endoscopic Score for Ulcerative Colitis – the SES-UC - Viktoria Bergqvist; Viktoria Bergqvist; Peter Gedeon; Erik Hertervig; Erik Hertervig; Jan Marsal; Jan Marsal; Jan Marsal (Frontiers in Gastroenterology)
Background & objectivesEndoscopy is the current gold standard for evaluation of disease activity in ulcerative colitis. The Mayo Endoscopic Subscore (MES) is commonly used for quantifying disease activity, but it has several weaknesses. Numerous new endoscopic indices have been developed but none of these have been widely implemented, likely due to limited feasibility. The primary objective of this study was thus to develop a simple, reliable, endoscopic index for ulcerative colitis. Secondary objectives were to evaluate and compare the MES, the Ulcerative Colitis Endoscopic Index of Severity (UCEIS), and the Ulcerative Colitis Colonoscopic Index of Severity (UCCIS), as well as examining the agreement between full colonoscopy and sigmoidoscopy.MethodsConsecutive adult ulcerative colitis patients had their routine colonoscopies video recorded, each edited into five shorter segment-specific video sequences. In parallel, blood, fecal, and mucosal samples were collected, together with data on symptoms and quality-of-life. The video sequences were scored by three gastroenterologists and one resident gastroenterologist according to a form comprising six endoscopic disease activity descriptors and an overall endoscopic disease severity assessment.ResultsOne hundred unique video sequences from twenty patients were each evaluated three times by four assessors, generating a total of 7200 unique segment-specific data-points for the six descriptors and 1200 unique assessments of overall endoscopic disease severity. The intra- and interobserver agreement for the individual descriptors were overall moderate to very good. The MES, UCEIS, and UCCIS performed similarly with the latter being slightly superior in terms of reliability and correlation to biomarkers of disease activity. The descriptor vascular pattern was the best discriminator at the lower end of the disease activity spectrum, whereas the descriptor ulcers was the best at the medium to high end. These two descriptors were combined into a new index, the Simple Endoscopic Score for Ulcerative Colitis (SES-UC), which displayed similar levels of reliability and accuracy as the established indices. Finally, comparison of sigmoidoscopy and colonoscopy showed that up to 38% of patients had their most inflamed segment located proximally to the sigmoid colon.ConclusionsWe propose a new simplified endoscopic index for ulcerative colitis, the SES-UC, which is based on the two descriptors vascular pattern and ulcers. The performance of the SES-UC was similar to, and in some regards better than, that of the established indices (MES, UCEIS, and UCCIS). This together with its simplicity makes SES-UC a candidate index for use in clinical practice as well as in clinical studies.